The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/curroncol29020067
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Clinical Significance of a Dyadic, Web-Based, Psychosocial and Physical Activity Self-Management Program (TEMPO) Tailored to the Needs of Men with Prostate Cancer and Their Caregivers: A Multi-Center Randomized Pilot Trial

Abstract: Background: Prostate cancer is the most common cancer diagnosis among men. Family caregivers (often female spouses) play a key role in ensuring patients’ needs are met, frequently assuming their role with no formal training, which can contribute to a high burden. The purpose of this study was to pilot TEMPO—the first dyadic, Tailored, wEb-based, psychosocial and physical activity self-Management PrOgram for men with prostate cancer and their caregivers. Methods: 49 men with prostate cancer and their caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Thirty‐six of 43 (84%) studies reported the proportion of participants who commenced the intervention out of the total number of eligible participants offered enrolment. The proportions were variable, ranging from 35 40 to 97% 41 for guided interventions with a mean of 68%, 36,37,40–52 and 20 50 ‐100% 51 for non‐guided interventions with a mean of 64% 7,34,38,39,53–69 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six of 43 (84%) studies reported the proportion of participants who commenced the intervention out of the total number of eligible participants offered enrolment. The proportions were variable, ranging from 35 40 to 97% 41 for guided interventions with a mean of 68%, 36,37,40–52 and 20 50 ‐100% 51 for non‐guided interventions with a mean of 64% 7,34,38,39,53–69 …”
Section: Resultsmentioning
confidence: 99%
“…The proportions were variable, ranging from 35 40 to 97% 41 for guided interventions with a mean of 68%, 36,37,[40][41][42][43][44][45][46][47][48][49][50][51][52] and 20 50 -100% 51 for non-guided interventions with a mean of 64%. 7,34,38,39,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Sixty-seven percent (29/43) of studies reported intervention usage, 19 of which (65.5%) were studies of non-guided interventions and 10 (34.5%) were guided (see Table S3, Appendix S1). Nine studies provided data on the proportion of participants using the intervention as intended, defined as 60%-100% completion in the literature.…”
Section: Engagement: Intervention Usagementioning
confidence: 99%
“… 10 11 Due to the deteriorating health of caregivers, their ability to provide support declines, which has a detrimental impact on the patients’ health. 12 Furthermore, the upward trend in prostate cancer incidence and the diverse treatment side effects pose a strain on the healthcare system, necessitating increased allocation of resources for the purposes of long-term care. This augmented burden consequently gives rise to extended patient waiting times, diminished availability of specialised care and escalated healthcare expenditures.…”
Section: Introductionmentioning
confidence: 99%
“… 14 However, they often lack structured training to acquire proficient management strategies, resulting in inefficient symptom control and potential exacerbation of harm due to suboptimal management practices. 12 A large-scale study conducted in the UK indicates that over 80% of males reported poor or very poor sexual function after treatment, with approximately 56% of males not receiving any interventions to address this issue. 15 Patients have reported unmet informational needs related to prostate cancer recurrence, the impact on their spouse/partner and long-term effects/recovery associated with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This review two studies(Lambert et al, 2022;Winters-Stone et al, 2016) presenting two interventions for survivors and their families.The TEMPO program, speci cally designed for men with prostate cancer and their caregivers, offered a comprehensive self-management curriculum encompassing psychosocial coping strategies and physical activity regimens(Lambert et al, 2022). The interventions targeting anxiety and quality of life demonstrated clinically signi cant improvements for both patients and caregivers, with promising adherence rates and positive outcomes across secondary measures(Lambert et al, 2022).…”
mentioning
confidence: 99%